The role of technological readiness in adopting AI for talent acquisition: Evaluating economic and operational performance - Mohammad, Anber Abraheem Shlash; Mohammad, Suleiman Ibrahim Shelash; Oraini, Badrea Al; Vasudevan, Asokan; Hunitie, Mohammad Faleh Ahmmad (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the absence of the application of Artificial Intelligence (AI) in Jordanian recruitment practices. In addition, current trends on "Talent Acquisition" and "Artificial Intelligence" in the Scopus database represent a shortage of research from Jordan, which demonstrates the difference in the utilization of AI in local Small and Medium Enterprises (SMEs) compared to international ones. Hence, this study addresses this gap by evaluating the AI acceptance of Jordanian SMEs in recruitment, emphasizing the technology's relative advantage, complexity, compatibility, cost, and perceived security and privacy. Furthermore, the study intends to determine how the adoption of AI has influenced the financial and operational aspects of the companies. A cross-sectional survey of managers from SMEs in Jordan was designed and implemented through an online survey to collect data. Ultimately, the data was analyzed using Structural Equation Modeling (SEM), where technology readiness was supported as necessary for implementing AI for talent management and its benefits for organizational sustainability.